The Effect of Three Types of Task Engagement Activities on Incidental Acquisition of Second Language Vocabulary - Davoud Amini (Journal of Modern Research in English Language Studies)
Cognition, motivation and affect are the three dimensions of mental functioning, each having a share in determining learning processes including second language acquisition. Despite the extensive effort to explore cognitive processes involved in task performance within task-based language teaching research, the effect of task-related emotional and motivational states on learning achievements is a fairly unexplored area. The study reported here investigated the comparative effects of cognitive, emotional and motivational engagement with a reading-while-listening task on incidental acquisition of L2 vocabulary. The three types of task engagement strategies were applied as pretask activities to task procedure. Multivariate analysis of covariance and follow-up-analyses revealed an enhancing effect for all three types of task engagement activities on immediate post-tests. However, the enhancement was not observed for measurements on delayed post-tests as a result of the remarkable decay in retention and ease of activation scores. Moreover, the effects of the three types of pre-task involvements were not differential. The findings have implications for integrating emotional, motivational and cognitive elements to form-focused tasks aimed at facilitating second language acquisition.